2022
DOI: 10.3390/diagnostics12010149
|View full text |Cite
|
Sign up to set email alerts
|

Review: Colon Capsule Endoscopy in Inflammatory Bowel Disease

Abstract: The COVID-19 pandemic has caused considerable disruption in healthcare services and has had a substantial impact on the care of patients with chronic diseases, such as inflammatory bowel disease. Endoscopy services were significantly restricted, resulting in long waiting lists. There has been a growing interest in the use of capsule endoscopy in the diagnostic pathway and management of these patients. This review explores the published literature on the role of colon capsule endoscopy in ulcerative colitis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Capsule endoscopy, which was authorized by the Food and Drug Administration (FDA) in 2001, enables a convenient and secure inspection of the gastrointestinal system. This technology has greatly revolutionized the treatment of small bowel disorders [ 44 ]. Studies have demonstrated that it can effectively display significant anatomical features of the esophagus and the entire stomach [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Capsule endoscopy, which was authorized by the Food and Drug Administration (FDA) in 2001, enables a convenient and secure inspection of the gastrointestinal system. This technology has greatly revolutionized the treatment of small bowel disorders [ 44 ]. Studies have demonstrated that it can effectively display significant anatomical features of the esophagus and the entire stomach [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…15 VCE has garnered attention as a minimally invasive diagnostic in various settings, particularly for evaluating and monitoring CD. [16][17][18][19][20] However, VCE's health-economic implications in CD surveillance remain understudied, 21 without evidence specific to Italian healthcare. We had previously shown VCE as a cost-effective alternative in the mid-to-long term in the United Kingdom and United States, with higher initial costs recouped through improved management over time, using a patient-level discrete-event simulation model.…”
Section: Introductionmentioning
confidence: 99%
“…As it is non-invasive and a comparatively more comfortable procedure than colonoscopy, it is also preferred by many patients for investigation of the colon 1 . The limited capacity for patient examinations during the COVID 19 pandemic 2 further propelled its use as it is less resource and time consuming. WCE has been established as a promising alternative for the diagnosis and monitoring of various diseases, including lesions such as polyps, tumors 3 , 4 , Ulcerative Colitis (UC) 5 , Chron’s disease 6 as well as other markers related to inflammatory bowel diseases such as inflammatory grading (occurrence of bleeding, ulcers, erosions), mucosal healing (edema, changes in mucosal vascularity), etc.…”
Section: Introductionmentioning
confidence: 99%